El peligro del subjetivismo ético-espiritual en el contexto de los abusos sexuales bajo falso misticismo: sobre la insuficiencia de la alteridad objetiva en la teología escrita de Javier Garrido Goitia - Marín Mena, Tomás J. (Estudios eclesiásticos, 2025)
The Spanish Tribunal of the Rota condemned Javier Garrido for «false mysticism». This offence refers to immoral actions contra sextum, but even more to a perverse theological legitimisation of such acts. This paper takes a first critical approach to Garrido’s thought and asks whether there are any theological elements that could facilitate sexual abuse in a climate of perverse mysticism. The research suggests that his theology is impregnated with a «subjectivism» (lack of alterity) which manifests itself especially in the privileging of individual interiority over ecclesial mediations, in a subtly relativistic ethical tendency, and in a certain gnostic immunity from sin. In the face of the danger or temptation of false mysticism, it is necessary to affirm the objectivity of moral acts. Finally, some theological-practical ideas are outlined to prevent the abuse of false mysticism and to deepen our understanding of its nature.